(untitled) (Modern education and development, 2025)
This article explores the concept of differential meaning in morphology, a semantic component that distinguishes words containing identical morphemes. Unlike denotational meaning, which refers to the direct referential content of a morpheme, differential meaning serves to differentiate words within the same morphological family. The study examines examples such as *bookshelf* vs. *bookcase* and *notebook* vs. *copybook*, where one morpheme carries the distinguishing semantic feature. Additionally, the article discusses cases where morphemes lack denotational meaning (e.g., *cran-* in *cranberry*) and function purely differentially. The analysis extends to bound morphemes in words like *receive*, *deceive*, and *perceive*, arguing that their prefixes may possess only differential meaning in a synchronic perspective. The findings highlight the importance of differential meaning in linguistic analysis and word formation.